Isolation and partial characterization of a novel virus from different carp species suffering gill necrosis – ultrastructure and morphogenesis. Issue 6 (19th July 2013) - Granzow, H; Fichtner, D; Schütze, H; Lenk, M; Dresenkamp, B; Nieper, H; Mettenleiter, T C
Abstract Two isolates of a novel enveloped RNA virus were obtained from carp and koi carp with gill necrosis. Both isolates behaved identically and could be propagated in different cyprinid cell lines forming large syncytia. The virus was sensitive to lipid solvents and neither exhibited haemadsorption/haemagglutination nor reverse transcriptase activity. Mature virus particles displayed a spherical shape with diameter of 100–350 nm after negative staining and 100–300 nm in ultrathin sections, covered by short projections of 8–10 nm in length. Maturation of virus progeny was shown to occur by budding and envelopment of the filamentous helical nucleocapsids at the cell surface. A detailed comparison of ultrastructure and morphogenesis of the novel virus isolates with selected arena‐, ortho‐ and paramyxoviruses as possible candidates for evaluation of taxonomic classification yielded no consistency in all phenotypic features. Thus, on the basis of ultrastructure the novel virus isolates could not be assigned unequivocally to any established virus family.